Carbon dioxide adsorption on coconut shell biochar. - Rebitanim, Nur Zalikha; Wan Ab Karim Ghani, Wan Azlina; Mohd Salleh, Mohamad Amran; Alias, Azil Bahari (2014)
Biochar has been acknowledged for its unique property which makes it potential candidates as adsorbent for carbon dioxide (CO2) in the flue gas system. In this study, the properties of raw coconut shell biochar (CSB) and amine treated coconut shell biochar (ACSB) are being compared. Physiochemical characterization has been performed to characterize the biochar properties. Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) were used to evaluate the functional groups and surface morphology of the biochar. Thermogravimetric analyzer (TGA) was used to discover the thermal properties, reactivity during adsorption. During the adsorption study, it was observed that amine treated coconut shell gasified at 800°C gave the highest adsorption of 35.57mgCO2/g sorbent at temperature of 30°C. Nitrogen functionalities and the basicity of samples increased after the amine treatment and is said to assist the adsorption capacity.